An enterprise collaborative management system: a case study of supplier selection in new product development. (1st September 2004) - Choy, K.L.; Lee, W.B.; Lau, Henry C.W.; So, Stuart C.K.; , Victor Lo
Businesses that remain competitive must not only look into their internal operations, but also communicate and work concurrently with all players in their supply chain network. In this paper, the supplier relationship management module of a server-based enterprise collaborative management system (ECMS) using enterprise application integration (EAI) technology for trial implementation at Honeywell Consumer Products (Hong Kong) Limited, is discussed. A case study using ECMS's supplier relationship management system (ISRMS) to integrate Honeywell's supplier rating system (SRS) and product coding system (PCS) via the case-based reasoning (CBR) technique, to select preferred suppliers during the new product development (NPD) process, is also reported here. It is found that the outsource cycle time, from the searching of potential suppliers to the allocation of orders, is greatly reduced. Through the ISRMS of ECMS, manufacturers identify preferred suppliers to form a supply network on which they depend for products, services and distribution effectively.